2008
DOI: 10.1590/s0001-37652008000100012
|View full text |Cite
|
Sign up to set email alerts
|

COL18A1 is highly expressed during human adipocyte differentiation and the SNP c.1136C > T in its "frizzled" motif is associated with obesity in diabetes type 2 patients

Abstract: Collagen XVIII can generate two fragments, NC11-728 containing a frizzled motif which possibly acts in Wnt signaling and Endostatin, which is cleaved from the NC1 and is a potent inhibitor of angiogenesis. Collagen XVIII and Wnt signaling have recently been associated with adipogenic differentiation and obesity in some animal models, but not in humans. In the present report, we have shown that COL18A1 expression increases during human adipogenic differentiation. We also tested if polymorphisms in the Frizzled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 43 publications
(33 reference statements)
0
20
0
2
Order By: Relevance
“…Promoter 2 of the Col18a1 gene, which is responsible for the production of the two longer variants, has been found to contain liver-specific regulatory elements (Lietard et al, 2000). Collagen XVIII is also expressed in fat tissue, and its expression level is increased during adipocyte differentiation (Inoue-Murayama et al, 2000;Errera et al, 2008). In hair follicles, collagen XVIII transcription is shown to be upregulated in bulge stem cells (Tumbar et al, 2004;Blanpain et al, 2004).…”
Section: Tissue Distribution Of Collagen XVIIImentioning
confidence: 99%
See 1 more Smart Citation
“…Promoter 2 of the Col18a1 gene, which is responsible for the production of the two longer variants, has been found to contain liver-specific regulatory elements (Lietard et al, 2000). Collagen XVIII is also expressed in fat tissue, and its expression level is increased during adipocyte differentiation (Inoue-Murayama et al, 2000;Errera et al, 2008). In hair follicles, collagen XVIII transcription is shown to be upregulated in bulge stem cells (Tumbar et al, 2004;Blanpain et al, 2004).…”
Section: Tissue Distribution Of Collagen XVIIImentioning
confidence: 99%
“…Proteolytic processing of the full-length frizzled variant has been shown to occur both in vitro, and in cancerous liver tissues in vivo, producing N-terminal peptides which contain the frizzled domain (Elamaa et al, 2003;Quelard et al, 2008). Moreover, polymorphism in the frizzled domain of the COL18A1 gene has been shown to be associated with a higher risk of obesity in type 2 diabetic patients (Errera et al, 2008).…”
Section: The Frizzled Variantmentioning
confidence: 99%
“…In addition, Errera et al (2008) have recently reported upregulation of COL18A1 gene expression during in vitro adipogenesis and genetic linkage between Frizzled polymorphisms and obesity. Furthermore, Hh and Wnt signaling have been demonstrated to be important regulators in adipocyte differentiation (Ross et al, 2000;Fontaine et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that if the level of endogenous inhibitors such as Endostatin, Angiostatin, Tumstatin, Thrombospondin or any antiangiogenic acting protein from chromosome 21 such as NC1 in plasma could be kept high at least for those few critical days, it might prevent distant angiogenesis while not interfering with wound healing. According to Errera et al, Endostatin is a fragment of NC1 [36]. According to Roh et al, Celecoxib and Indomethacin are also effective in preventing wound healing associated tumor growth so those drugs may be also considered in the list [37].…”
Section: Hypothesis – Primary Antiangiogenic Therapy Proposedmentioning
confidence: 99%